The relationship between macroeconomic indicators and stock returns: evidence from the JSE sectoral indices - Dlamini, Cebisa S (My University, 2017)
This study investigates the causal relationship between selected macroeconomic indicators (inflation, industrial production, South African (SA) short term interest rate, United States (US) short term interest rate) and the Resources, Financials and Industrials sectoral indices of the Johannesburg Stock Exchange (JSE) using monthly data over the period January 2002 to January 2016. The Granger-causality test is used to determine whether a causal relationship exists between the macroeconomic indicators and the sectoral indices. The results found the following: a uni-directional causal relationship from the Resources index to the US short term interest rate; a uni-directional causal relationship from the Financials index to the SA short term interest rate and the US short term interest rate; and a uni-directional causal relationship between the Industrials index and inflation, Industrials index and US short term interest rate, Industrials index and SA short term interest rate, Industrial production and the Industrials index. Further, the results show that only the SA short term interest rate and gold price jointly impact the Resources index, negatively and positively, respectively. Also, SA short term interest rate and US short term interest rate have a negative and positive joint impact the Financials index. Inflation, industrial production and gold price are restricted in the multiple regression model. These findings have important implications for managing resources and the macroeconomy.
Thesis submitted in fulfillment of the requirements for the degree of Master of Management in finance and investment 2017